Modes of dying of children in Intensive Care Units in Spain: MOMUCIP study - María Carmen Agra Tuñas; Francisco Javier Pilar Orive; Elva Rodríguez Merino; Jesús López-Herce Cid; Gema Manrique Martín; Paula García Casas; Arturo Hernández González; Carmen Ramil Fraga; Corsino Rey Galán; María Rosario Riestra Rodríguez; Ramón Hernández Rastrollo; Francisco Fernández Carrión; et al. (Elsevier, 2019)
Objective: To describe the different types of child deaths in Paediatric Intensive Care Units (PICU) in Spain, and to analyse the characteristics of those dying from a limitation of therapeutic effort (LET). Method: A multicentre retrospective study by conducted by reviewing the hospital discharge reports corresponding to deceased patients in 8 Spanish PICUs between 2011 and 2017. Results: A total of 337 deaths were recorded, of which 151 (50.7%) occurred after a decision of LET, while 114 (33.8%) were due to an indicated, but failed, cardiopulmonary resuscitation, and 52 (15.4%) were due to brain death. The most common causes of hospital admission for those children that finally died were a heart-related problem (32.6%) or a respiratory problem (22.6%).A total of 86 cases (25.5%) had a previous hospital admission, with 253 cases (75%) suffering from some type of chronical illness, and 78 (23%) had a serious disability at the time of the admission.LET cases were more frequent among these children and those suffering from cancer. The predominant LET type consisted in: not starting the CPR in the event of a cardiac arrest (45%), withdrawal of the respiratory support (31.6%), and withdrawal of vasoactive drugs (21.6%). Conclusions: At the present time, at least half of the children dying in a PICU in Spain die after a LET decision, which is more frequent in those patients with previous hospital admissions, with a serious incapacity, and chronic or oncological disease. Health professionals should be aware of this situation, and be prepared to share decisions with the families, and to offer children at the end of their life the best possible caring quality. Resumen: Objetivo: Describir los modos de muerte de los niños en las Unidades de Cuidados Intensivos Pediátricos (UCIP) en España y analizar las características de aquellos que fallecen tras decidir una limitación del esfuerzo terapéutico (LET). Métodos: Estudio retrospectivo multicéntrico mediante revisión de informes de alta de los pacientes fallecidos en 8 UCIPs españolas entre 2011 y 2017. Resultados: Se recogieron 337 fallecimientos, de los cuales 151 (50,7%) ocurrieron durante una decisión de LET, mientras que 114 (33,8%) fueron por reanimación cardiopulmonar indicada pero fallida (FRCP) y 52 (15,4%) por muerte cerebral. Los motivos más frecuentes de ingreso en los niños que luego fallecieron fueron cardíacos (32,6%) y respiratorios (22,6%). El 25,5% (86 casos) habían tenido ingresos previos, 253 (75.1%) padecían enfermedades crónicas y 78 (23,2%) presentaban al ingreso una discapacidad grave. La LET fue más frecuente en estos niños y en aquellos con cáncer. La LET consistió fundamentalmente en no iniciar la RCP en caso de parada cardíaca (45%), retirada de la ventilación mecánica (31.6%) y retirada de fármacos vasoactivos (21.6%). Conclusiones: En el momento actual al menos la mitad de los niños que fallecen en una UCIP en España lo hacen tras una decisión de LET, que es más frecuente en aquellos con ingresos previos, discapacidad grave, enfermedad crónica u oncológica. Los profesionales debemos ser conscientes de esta realidad y prepararnos para compartir las decisiones con las familias y ofrecer la mejor calidad asistencial posible a los niños al final de su vida.